The Role of Non- Profit Organizations in Building the Capacity of their Beneficiaries - Alsabilah, Meshari Abdulhadi (Journal of Humanities & Social Sciences, 2021)
The study aimed to mainly identify the role of non- profit organizations in building the capacity of their beneficiaries. The study relied on the social survey approach and used the questionnaire as a tool to realize the purpose of the study. The survey population was (1353) beneficiaries who attended the capacity building program, offered by five different organizations across the Kingdom. They were selected using the simple random sample (SRS) method. The study found a number of results, the most important of which was that the survey population believed that they benefited from the capacity building program in general. The study also showed statistically significant differences in the degree to which the trainees benefited from the capacity building program, according to the organization that offered the program. The study recommended several measures, the most important of which are: Non- profit organizations should develop programs that aim to develop and market the beneficiaries products and link them to e- commerce websites. Non- profit organizations should develop an electronic application to provide training, guidance and development programs in order to foster communication with beneficiaries to enable their capacity in a more impactful way.
Keywords: non-profit organizations; self-employment; social development; role theory